pengaruh kualitas pelayanan receptionist terhadap kepuasan tamu di hotel pusako bukittinggi - yandri andika rahmat (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Abstract This study aims to determine the effect of the quality of receptionist services on guest satisfaction at the Pusako Hotel Bukittinggi. This type of research is quantitative descriptive with associative causal methods. The purposive sampling used as many as 93 guests who had or were staying at Pusako Bukittinggi Hotel In the period of January-June 2017, data was collected through questionnaires with a Likert scale that had been tested for validity and reliability. The results obtained from this study are as follows: 1) Service Quality of Hotel Employees is in the poor category with a percentage value (58%), 2) Guest Satisfaction is in a less satisfied Category at Pusako Bukittinggi Hotel with a percentage value (53%). 3) The results of a simple linear regression test obtained a value of Fcount 29,667 with sig. 0,000 <0,05 which means that variable X can explain Y variable significantly. Furthermore, the regression coefficient is 0.383 at a significant level of 0.000 <0.05. This means that each increase of 1 unit of service quality will increase 0.383 guest satisfaction units, and the R square value of 0.246 means that the effect of variable X on Y variable is 0.246 (24.6%) while the remaining 75.4% is influenced by other factors. So the service quality variable affects the guest satisfaction variable, so Ha is accepted. Keywords: Service Quality, Guest Satisfaction